Reliability of BGAs and Mixed Low Temperature Solder Assemblies - Ghaffarian, Reza; Meilunas, Michael (InterSociety Conference on Thermal and Thermomechanical Phenomena in Electronic Systems, 2023)
This paper presents two key aspects of reliability of ball grid array (BGA) technologies: one aspect for high-reliability (HR) and the other for commercial applications. For HR, it presents the effect of isothermal aging at BGA component level to address a burn-in requirement for die screening per Military standard specification. Pull and shear behavior of BGAs with tin-lead and SAC305 solder balls were presented for fresh and burn-in conditions ( 125^{°}C and 150^{°}C for 240 hr). These were assembled onto PCBs and then subject to thermal cycling (TC) between 40^{°}C and 105^{°}C . Cycles-to-failures (CTFs) in Weibull plots were presented for the SnPb CABGA208 assemblies with micro-sectioned images, The commercial aspect covered low temperature solder ball and solder paste for assembling BGAs and other components. Two types of low temperature BiSn alloys, either Cu/Ni or Ag additives and with 139^{°}C/174^{°}C solidus/liquidus temperatures, were evaluated. The mixed hybrid configuration utilized SAC305 BGAs using the SnBiAg solder paste. The low temperature assemblies were subjected to two TCs (-40^{°}C/105^{°}C and 0^{°}C/105^{°}C) . CTF results are presented for CABGA208 with failure analysis by X -sectional evaluation.